A Sense of Time(ly) Seeing in DeLillo’s Later Novels - Stefania Iliescu (Transatlantica)
This article sets out to examine the ways in which Don DeLillo uses ekphrasis in his later novels to explore new modes of perceiving reality through screens; these perceptual modes allow readers to discover the effects produced by the hybridization of reality, and to experience how media and technological devices distort both the perception of time and experiential reality. The quality of perceptual experiences lies at the core of the writer’s aesthetics, which builds on the ability of language to convey the subjective perception of the characters, as well as the sensations and emotions that shape their mental lives and actively involve their sensing bodies, in an attempt to elicit readers’ empathic responses and their ethical engagement with the narrative contents. Unlike his novels published before 2000, where the presence of images leads to a phenomenon of hyperreality, DeLillo’s later fiction develops a rhetoric of seeing which gives rise to a reading experience that has the power to reveal the present to the readers. Readerly involvement resides, I argue, in the reader-cum-viewer position and the tension that develops from the interplay between the characters’ embodied act of seeing and the readers’ responses in relation to the narrative framing of the scene; the reading experience thus acquires emotional relevance. Reading, just as viewing, becomes a lived, embodied experience that allows readers to experience the characters’ subjective perception of time, and decide whether they feel with the characters or choose to block out empathic responses.